A COMPREHENSIVE OVERVIEW OF PROTOCOLS AND PRACTICES FOR NURSING HEALTH ASSISTANTS IN ENVIRONMENTAL HEALTH AND SAFETY IN HEALTHCARE SETTINGS - 1Alhassan Ali Salem Al Zulayq, 2Saleh Ali Salem Al-Zulaiq, 3Salem Nasser Mohammed Al khamsan, 4Ali Mohammed SalehAl khamsan, 5Nasser Saleh Mesfer Al Khamsan, 6Salem Mohammed Saleh ALKhomsan, 7Hadi Mahdi Alkhamsan, 8Muhammad Mahdi Hussein Al-Yami, (Chelonian Research Foundation, 2022)
This paper provides a comprehensive overview of protocols and practices for nursing health assistants (NHAs) in environmental health and safety (EHS) within healthcare settings .This study highlights the significance of EHS measures in healthcare, surveys pertinent writing, summarizes strategies utilized in EHS forms, presents discoveries by counting pictures, tables, and figures, examines what comes about, draws conclusions, and offers suggestions to bolster NHA's EHS convention. From this audit, it is evident that guaranteeing a solid EHS plan is fundamental to ensuring healthcare laborers and patients and, hence, optimizing utilization solidly. Keywords: Nursing health assistants, environmental health and safety, Healthcare settings, Protocols, Practices